A comparative study to evaluate the effect of honey dressing and silver sulfadiazene dressing on wound healing in burn patients - Baghel, P. S. (Medknow Publications, 2009)
To compare the effect of honey dressing and silver-sulfadiazene (SSD) dressing on wound healing in burn patients. Patients (n=78) of both sexes, with age group between 10 and 50 years and with first and second degree of burn of less than 50% of TBSA (Total body surface area) were included in the study, over a period of 2 years (2006-08). After stabilization, patients were randomly attributed into two groups: ‘honey group’ and ‘SSD group’. Time elapsed since burn was recorded. After washing with normal saline, undiluted pure honey was applied over the wounds of patients in the honey group (n=37) and SSD cream over the wounds of patients in SSD group (n=41), everyday. Wound was dressed with sterile gauze, cotton pads and bandaged. Status of the wound was assessed every third and seventh day and on the day of completion of study. Patients were followed up every fortnight till epithelialization. The bacteriological examination of the wound was done every seventh day. The mean age for case (honey group) and control (SSD group) was 34.5 years and 28.5 years, respectively. Wound swab culture was positive in 29 out of 36 patients who came within 8 hours of burn and in all patients who came after 24 hours. The average duration of healing in patients treated with honey and SSD dressing at any time of admission was 18.16 and 32.68 days, respectively. Wound of all those patients (100%) who reported within 1 hour became sterile with honey dressing in less than 7 days while none with SSD. All of the wounds became sterile in less than 21 days with honey, while tthis was so in only 36.5% with SSD treated wounds. The honey group included 33 patients reported within 24 hour of injury, and 26 out of them had complete outcome at 2 months of follow-up, while numbers for the SSD group were 32 and 12. Complete outcome for any admission point of time after 2 months was noted in 81% and 37% of patients in the honey group and the SSD group. Honey dressing improves wound healing, makes the wound sterile in lesser time, has a better outcome in terms of prevention of hypertrophic scarring and post-burn contractures, and decreases the need of debridement irrespective of time of admission, when compared to SSD dressing.